Reducing the failures with adding glass insulators to composite insulators of 400 kV transmission line at high altitude. (November 2022) - Alboyacı, Bora; Çınar, Mehmet Aytaç; Demirol, Yunus Berat; Uzar, Mete
Abstract: Using composite insulators instead of glass insulators in high voltage transmission lines has become common with rapid developments in material technology. This study examined the 270 km long İspir-Bağıştaş high voltage line with a 400 kV composite insulator, which was commissioned in 2016. The altitude along the transmission line route varies between 860 and 2800 meters. After the line was commissioned, too many phase-earth failures were experienced. To reduce failures, the Turkish Electricity Transmission Corporation (TEİAŞ) operator added glass insulators to the existing composite insulators. It was observed that the number of failures decreased significantly after the addition. That study aims to find the most suitable location and the number of glass insulators. Since the design of the insulation system is crucial for network reliability and sustainability, it has become a necessity today to carry out analysis before the design stage. In this context, the pole-insulator systems used in the transmission lines were modelled in the Ansys Electronic Suite finite element analysis program. The influence of the conditions applied in the field was examined. Accordingly, when one, two and three glass insulators are added to the conductor side, the maximum electric field distributions on the composite insulator surface decrease by 19%, 35% and 45%, respectively. In the case of adding glass insulators to the pole side, there is no significant change in the electric field distribution formed on the composite insulator surface. In addition, when adding one, two and three glass insulators, the minimum arc distances increase by approximately 12%, 19% and 21%, respectively. Accordingly, adding three glass insulators to the composite insulator would be appropriate to reduce the failures without changing the composite insulators. Although the electric field decreases up to 45% when glass insulators are added to the conductor side, it would be convenient to add them to the pole side for easy application on the field. Due to the arc distances, it is not recommended that the number of glass insulators is added by more than three for the examined system. The number of faults in the line decreased by 82% in the first twelve months following the addition of the glass insulator to the pole side, which shows the benefit of the application. That application is essential in terms of reducing the problems in live lines without changing existing insulators. Graphical abstract: Highlights: Adding glass insulators to existing composite insulators reduces the maximum electric field distribution on the insulator surface up to 45%. Adding glass insulators to existing composite insulators increases the minimum arc distance up to 21%. In the 12 months following the addition of glass insulators to existing composite insulators, the number of failures decreased by 82%. The influence of the altitude correction factor should be considered according to the IEC 60071-1 standard. When the corona ring is not used, the maximum electric field strength on the composite insulator surface increases to 5.8 times.